2017
DOI: 10.3390/jcm6020022
|View full text |Cite
|
Sign up to set email alerts
|

CVD and Oxidative Stress

Abstract: Nowadays, it is known that oxidative stress plays at least two roles within the cell, the generation of cellular damage and the involvement in several signaling pathways in its balanced normal state. So far, a substantial amount of time and effort has been expended in the search for a clear link between cardiovascular disease (CVD) and the effects of oxidative stress. Here, we present an overview of the different sources and types of reactive oxygen species in CVD, highlight the relationship between CVD and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
138
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(146 citation statements)
references
References 173 publications
5
138
0
3
Order By: Relevance
“…Accordingly, the present study found a significant positive correlation between serum XO and NOX activities in ACS patients. This observation suggested that both XO and NOX activities increased in patients synergistically for the establishment of oxidative stress, as reported earlier [37]. A similar conclu-sion can be drawn from the positive correlations between MPO and RBC lysate XO in both ACS patients and control subjects, since MPO is also an enzyme responsible for catalyzing the formation of ROS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Accordingly, the present study found a significant positive correlation between serum XO and NOX activities in ACS patients. This observation suggested that both XO and NOX activities increased in patients synergistically for the establishment of oxidative stress, as reported earlier [37]. A similar conclu-sion can be drawn from the positive correlations between MPO and RBC lysate XO in both ACS patients and control subjects, since MPO is also an enzyme responsible for catalyzing the formation of ROS.…”
Section: Discussionsupporting
confidence: 85%
“…It has been found that the main sources of CVD-ROS are NOX and XO [37]. In oxidative stress, they are the ones producing excessive superoxide in ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cardiomyocytes membranes are rich in phospholipids that are especially susceptible to OS, which leads to an elevation in the level of lipid peroxidation production, resulting in structural changes and dysfunctional in the cardiac muscle. Previous authors reported that exposure to free radicals induced heart injury, energy production failure, an elevation in the resting tension and promoted levels of lipid peroxidation . This is in parallel with our experimental result that evidenced by an augment in the level of MDA as a potent marker of lipid peroxidation, associated with the deregulation of thioredoxin antioxidant system, reduction of GSH content, as well as a decline in the activity of SOD, CAT, and GPx.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress occurs as a result of redox imbalances when the production of destructive free radicals, such as reactive oxygen species, surpasses the antioxidant defenses . Oxidative stress is implicated in the expression of inflammatory mediators and the regulation of cellular events, leading to various diseases such as cardiovascular disease, diabetes and periodontitis . One of the functions of PON1 is the reduction of oxidative stress, which strengthens our hypothesis that PON1 affects the homeostasis of PDL tissue.…”
Section: Discussionsupporting
confidence: 79%